MicroRNAs and thyroid hormone action. (5th April 2021) - Aranda, Ana
Abstract: MicroRNAs (miRNAs) are small noncoding RNAs that post-transcriptionally repress gene expression by binding generally to the 3′-untranslated regions of their target mRNAs. miRNAs regulate a large fraction of the genome, playing a key role in most physiological and pathological processes. The thyroid hormones (T4 and T3) are major regulators of development, metabolism and cell growth. The thyroid hormones (THs) are synthetized in the thyroid gland and enter the cells through transporter proteins. In the cells, T4 and T3 are metabolized by deiodinase enzymes and bind to nuclear receptors (TRs), which have a higher affinity by T3. TRs act as hormone dependent transcription factors by binding to thyroid hormone response elements (TREs) in the target genes and recruiting transcriptional coregulators. There is increasing evidence that a variety of miRNAs target deiodinases and the receptor, thus regulating TH signaling is different tissues. In turn, the THs have been shown to modulate the expression of specific miRNAs and their mRNA targets in different cell types and organs. In many cases, the existence of TREs in the regulatory regions of these miRNAs has been identified, and the hormone bound receptors transcriptionally regulate expression of these molecules. Changes in the levels of miRNAs have been demonstrated to mediate some of the important actions of the THs in processes such as muscle and heart function, lipid liver metabolism or skin physiology. In addition, miRNA regulation is involved in the effects of TRs on cell proliferation and cancer. Highlights: microRNAs post-transcriptionally regulate a large fraction of the genome. The thyroid hormone receptors act as hormone-dependent transcription factors. Diverse microRNAs control receptor levels and intracellular thyroid hormone metabolism. The hormone bound receptors control expression of microRNAs with important functions in different tissues.